Attention deficit hyperactivity disorder in adults (Portuguese Journal of Family Medicine and General Practice, 2004)
People suffering from ADHD are more likely than the general population to experience certain difficulties and suffer accidents, carelessness. The ADHD arises often associated with other psychiatric disorders.